Child‐Care Subsidies and School Readiness in Kindergarten. Issue 5 (5th March 2013) - Johnson, Anna D.; Martin, Anne; Brooks‐Gunn, Jeanne
Abstract : The federal child‐care subsidy program represents one of the government's largest investments in early care and education. Using data from the nationally representative Early Childhood Longitudinal Study–Birth Cohort, this study examines associations, among subsidy‐eligible families, between child‐care subsidy receipt when children are 4 years old and a range of school readiness outcomes in kindergarten (sample n ≈ 1, 400). Findings suggest that subsidy receipt in preschool is not directly linked to subsequent reading or social‐emotional skills. However, subsidy receipt predicted lower math scores among children attending community‐based centers. Supplementary analyses revealed that subsidies predicted greater use of center care, but this association did not appear to affect school readiness.